PENGARUH KUALITAS PRODUK, TEMPAT, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PAKAIAN BEKAS DI PASAR SEKEN AVIARI KOTA BATAM - Silalahi, Rudi Yanto Batara; Susantri, Letanli Ayu (REKAMAN (Jurnal Riset Ekonomi Bidang Akuntansi dan Manajemen), 2018)
The purpose of this study Â to determine the influence of product quality partially to purchase decision, to determine the influence of place partially to purchase decision, to determine the influence of prices partially purchase decision, and to determine the influence of quality, place, and price on the purchase decision second clothes at Aviari Second Market in Batam City. The type of research used is quantitative with associative properties. Analytical technique used to test the hypothesis with multiple linear regression analysis. The sample of research is 145 people by using accidental sampling technique. The result of this research is the quality of the product partially significant influence on the purchase decision with sig 0.007 <0.05, the place partially significant influence on the purchase decision with sig 0.023 <0.05, the price partially significant influence on purchasing decision sig 0.000 <0.05, and based on F test results, product quality, place and price simultaneously have a significant influence on purchasing decision with sig 0.000 <0,05.